STUDY OF EFFECTIVENESS AND SIDE EFFECTS OF FAVIPIRAVIR THERAPY ON MILD AND MODERATE COVID-19 PATIENTS - Didik Hasmono; Alfa Frista Arta; Ismawati; Ruddy Hartono; Mohammad Subhan (Jurnal Kesehatan, 2022)
Introduction: Corona Virus Disease-2019 (COVID-19) is divided into five degrees that are asymptomatic, mild, moderate, severe and critical. Recently, Favipiravir known as off-label antivirals for COVID-19 that inhibits RNA-dependent RNA polymerase (RdRp) and is administered orally 2x1600 mg as loading dose and 2x600 mg as a maintenance dose. Methods: This observational retrospective study aims to determine effectiveness (PCR/Rapid Ag, temperature, respiratory rate, oxygen saturation, and chest X-ray) and side effects (digestive, uric acid, liver, blood, glucose, and lipids profile) of Favipiravir in mild and moderate COVID-19; which inclusion criteria were Favipiravir (5-10 days); a group of antibacterials: Azithromycin (therapy A), Levofloxacin (therapy B), and combination (therapy C); vitamins, minerals, symptomatic and comorbid therapy; and Fondaparinux used in moderate degree then described quantitatively. Results: This study obtained 47 HMR dominated by males (55%), aged 19-30 years (36%), cough symptoms (72,3%), and no comorbid status (70.2%). Favipiravir (6-7 days) is effective for mild and moderate degree in all effectiveness parameters with average length in mild degree was 6-12 days and moderate degree was 8-13 days. Possible interaction with Paracetamol was found. Most side effects were diarrhea and no significant side effects were found on liver profile (AST and ALT), glucose profile, and blood profile (leukocytes and erythrocytes). Conclusions: This result suggests that increasing collaboration of pharmacists with other healthcare in monitoring the use of Favipiravir related to interactions, uric acid, and lipid profiles, also effects in patients under 18 years, men, and elderly is important.